Nuclear Receptor Interacting Protein-2 Mediates the Stabilization and Activation of β-Catenin During Podocyte Injury - Hou, Qing; Le, Weibo; Kan, Shuyan; Shi, Jinsong; Lang, Yue; Liu, Zhihong; Chen, Zhaohong (Frontiers in Cell and Developmental Biology, 2021)
Abstract Objective: Activation of β-catenin causes podocyte injury and proteinuria, but how β-catenin signalling is regulated during podocyte injury remains elusive. Nuclear receptor interacting protein 2 (NRIP2) modulates the Wnt pathway in colorectal cancer-initiating cells, but the role of NRIP2 in podocyte injury has not yet been investigated. We aimed to examine the interaction between NRIP2 and β-catenin signalling. Materials and Methods: Knockdown or overexpression of NRIP2 and β-catenin and chemical treatments were performed in cultured human podocytes. Immunoprecipitation, immunoblotting and immunofluorescence assays were used to assess protein interactions and expression. Data from the GEO dataset and kidney tissues from patients with focal segmental glomerulosclerosis (FSGS) and surgical nephrectomy were examined. An adriamycin (ADR) nephropathy model was established in NRIP2 knockout mice. Results: NRIP2 knockdown accelerated β-catenin degradation, which was reversed by MG132; specifically, NRIP2 bound β-catenin and stabilized it to prevent its degradation through the ubiquitin proteasomal pathway. Overexpression of NRIP2 led to β-catenin activation and Snail1 induction, and these effects were attenuated by β-catenin knockdown. NRIP2 knockdown blocked ADR-stimulated β-catenin activation. In ADR mice, genetic knockout of Nrip2 ameliorated podocyte injury and loss, glomerulosclerosis, and proteinuria by inhibiting β-catenin activation. Moreover, NRIP2 was significantly upregulated in podocytes of FSGS patients and colocalized with nuclear β-catenin. Conclusion: These results established NRIP2 as a stabilizer of β-catenin activation through the ubiquitin proteasomal pathway in podocyte injury.